Analisis Lingkungan Positif dalam Mendukung Pembelajaran Efektif dan Pengelolahan Kelas yang Harmonis di SMA Negeri 1 Gedeg - Dina Dwi Febriani; Resty Tri Mahanani; Amellia Fitri Nafidhatus S; Ardiansyah Fahmi Satria; Mus Shafira Ramadhani Yapono; Eva Apriyani Mahmud (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
A positive school environment is essential to support individual learning and growth and create effective and productive learning experiences. Good classroom management is also crucial for creating conducive conditions, removing barriers and providing facilities that support students' development according to their social, emotional and intellectual needs. This study used a qualitative method with questionnaire and interview instruments to collect descriptive data from students and teachers. The results showed that in class XII IPA, a conducive classroom atmosphere plays a big role in supporting learning, while in class XI IPS, effective classroom management is more important to create a safe and comfortable environment. Non-academic activities, such as the JB4 program, increased student engagement and improved the school environment. Overall, the collaboration between teachers, students and school programs creates an environment that supports optimal student development.